The Hidden Cost of Buoyancy: Environmental and Social Consequences of EPS in Marine Aquaculture - Eun, Jiho (Technium Sustainability, 2026)
Plastic buoy pollution, particularly from expanded polystyrene (EPS), has emerged as a major environmental threat, impacting marine ecosystems, aquaculture, and human health. This study examines microplastic contamination from EPS buoys, focusing on South Korea’s oyster farms in Tongyeong and Jeju Island’s coastal economy. It highlights bioaccumulation in filter-feeding organisms, disruptions to biodiversity, and the disproportionate burden placed on low-income communities. Institutional inertia and inadequate waste management systems hinder reform, necessitating a transition to biodegradable alternatives. By proposing an eco-friendly buoy design, this research advocates for systemic change in marine infrastructure, governance, and sustainable seafood production.